(untitled) (SCIENCE TIME JOURNAL, 2026)
This methodological article examines the second language acquisition (SLA) processes of two adult learners from Central Asia through a comparative qualitative case-study approach. The research focuses on how motivation, age, instructional background, and affective factors influence the development of linguistic competence, particularly in morphology and syntax. The learners, Lola and Almaz, demonstrate contrasting learning trajectories shaped by deductive and inductive learning strategies, investment, and sociocultural identity. Drawing on established SLA theories such as motivation and investment, affective filter hypothesis, and age-related cognitive factors, the study highlights strengths and weaknesses in learners’ grammatical accuracy and communicative confidence. The findings suggest that balanced instruction, supportive learning environments, and task-based methodologies significantly contribute to effective adult language learning. Pedagogical implications are provided for English language teachers working with adult learners in multilingual contexts.